Assessment of genetic diversity in a highly valuable medicinal plant Catharanthus roseus using molecular markers - Ranjan Kumar Shaw; Laxmikanta Acharya; Arup Kumar Mukherjee (Crop Breeding and Applied Biotechnology, 2009)
Genetic diversity was evaluated among 14 cultivars of Catharanthus roseus using RAPD and ISSR markers.The RAPD primers resulted in the amplification of 56 bands, among which 46 (82%) bands were polymorphic Four ISSRprimers amplified 31 loci out of which 17 were polymorphic and 14 are monomorphic. The Jaccard's similarity derived fromthe combined marker system showed that the varieties First Kiss Coral and Cooler Orchid were the most closely relatedcultivars, with 98% similarity. In the dendrogram constructed on the basis of both RAPD and ISSR data two clear clusterswere obtained. The smaller cluster included C. roseus Cv Blue Pearl and C. roseus Cv. Patricia White and the larger clusterwas subdivided into two sub clusters with C. roseus Cv. First Kiss Polka Dot isolated from the rest of the cultivars. This maybe useful for breeding for improved quality.